The Role of digital Based Learning (PBL) Technology in Islamic Learning in the Kurikulum Merdeka - Khairunnisa, Nur Afifah; Dartim, Dartim (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
The Role of Technology in Problem-based Learning for Quality Islamic Religious Education within the scope of the Independent Curriculum (Kurikulum Merdeka), a new curriculum implemented in the education system in Indonesia, involves training students to solve problems. Using the Problem-Based Learning model can enhance students' critical thinking skills, especially in problem-solving. This research employed a qualitative approach, a process to sift through words whose key elements could be extracted and developed, focusing on discussing the implications of technology in Islamic religious education in the era of digitization. The analysis aimed to understand the implications of technology on Islamic religious education, especially in the current era of strong digitization, progress, technological advancements, and modernization, where approximately 60% of life relies on technology. Thus, the significant role that can make Islamic Religious Education quality is through technology-based Problem-Based Learning. This research analysis focuses on the context of quality Islamic Religious Education. Data required for this study were gathered through observation and data analysis, news, opinions, and journals from official websites. This research explains that with technology integration, Islamic Religious Education becomes a quality learning experience, further enhanced by the current independent curriculum, which allows students to choose their interests and talents freely, provided teachers guide and monitor them. The advancements in Information and Communication Technology have facilitated numerous changes, including the emergence of Problem-Based Learning in the field of education.